Practical trade‐offs for the prefix‐sum problem. (22nd October 2020) - Pibiri, Giulio Ermanno; Venturini, Rossano
Abstract: Given an integer array A, the prefix‐sum problem is to answer sum ( i ) queries that return the sum of the elements in A [0.. i ], knowing that the integers in A can be changed. It is a classic problem in data structure design with a wide range of applications in computing from coding to databases. In this work, we propose and compare practical solutions to this problem, showing that new trade‐offs between the performance of queries and updates can be achieved on modern hardware.